1999
DOI: 10.1061/(asce)0733-9399(1999)125:1(79)
|View full text |Cite
|
Sign up to set email alerts
|

New Approximations for SORM: Part 1

Abstract: In the second-order reliability method the principal curvatures, which are defined as the eigenvalues of rotational transformed Hessian matrix, are used to construct a paraboloid approximation of the limit state surface and compute a second-order estimate of the failure probability. In this paper, the accuracy of the previous formulas of SORM are examined for a large range of not only curvatures but also number of random variables and first-order reliability indices. For easy practical application of SORM in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…A more accurate three‐term formula was proposed by Tvedt , who also derived exact results for a paraboloid as well as all the quadratic forms of Gaussian variables . These and later formulations require the principal curvatures of the limit state surface at the design point to be solved. The conventional approach involves the computation of the second‐order derivative matrix.…”
Section: Brief Review Of the Second‐order Reliability Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more accurate three‐term formula was proposed by Tvedt , who also derived exact results for a paraboloid as well as all the quadratic forms of Gaussian variables . These and later formulations require the principal curvatures of the limit state surface at the design point to be solved. The conventional approach involves the computation of the second‐order derivative matrix.…”
Section: Brief Review Of the Second‐order Reliability Methodsmentioning
confidence: 99%
“…Under certain conditions, some of the SORM formulas may breakdown (e.g., Tvedt and Breitung formulas require κ ⩾ − 1/ β ; Hohenbichler–Rackwitz and Hong formulas require κ ⩾ [Φ( β ) − 1]/ϕ( β )). Zhao and Ono investigated four of the formulas, namely Tvedt, Breitung, Koyluoglu, and Cai, and concluded that they worked well for cases involving small curvatures or a small number of random variables. Significant errors may arise if otherwise, or for limit state surface having curvatures of different signs.…”
Section: Example 2: Bearing Capacity Of Shallow Footingmentioning
confidence: 99%
“…Posteriormente, outros autores realizaram aproximações com base na mesma ideia de equações quadráticas (TVEDT, 1983;CAI;ELISHAKOFF, 1994;KÖYLÜOǦLU;NIELSEN, 1994;ZHAO;ONO, 1999).…”
Section: Sorm -Second Order Reliability Methodsunclassified
“…This is for instance the case in certain problems dealing with reliability-based design and response surface methodology, see e.g. Reference [1].…”
Section: Introductionmentioning
confidence: 98%